TruCutR needle biopsy in asbestosis and silicosis: correlation of histological changes with radiographic changes and pulmonary function in 41 patients. Issue 4 (November 1978) - Tukiainen, P; Taskinen, E; Korhola, O; Valle, M
Abstract : A percutaneous needle biopsy was performed with a TruCut needle on 41 patients with suspected pneumoconiosis. Patients selected for biopsy tended to have brief or unusual dust exposure, as well as questionable radiographic opacities. Sixteen had been exposed to asbestos, 13 to silica and 12 to mixed dust containing quartz, coal, iron, asbestos and talc. All patients in the asbestos group and most in the other two groups had a reduced transfer factor. Most patients in the asbestos group and about 25% of the other patients had restrictive ventilatory impairment. Chest radiographs were assessed according to standard films of the ILO U/C International Classification (International Labour Office, 1972). In 25 patients radiographic opacities were absent or acanty (categories 0--1/1). The dominant radiographic feature of many patients exposed to asbestos was a ground-glass appearance or a bilateral elevation of the diaphragm, or both, features difficult to assess according to the ILO U/C scheme. Most histological changes were those usually seen in pneumoconiosis. However, in only two patients with silicosis were silicotic nodules detected. The specimens of seven patients showed a granulomatous inflammation. The severity of alveolar wall involvement correlated well with the transfer factor value but poorly with radiographic changes. The profusion of radiographic opacities also correlated poorly with functional impairment. As a diagnostic tool the needle biopsy was valuable in asbestosis and slightly less so in mixed-dust fibrosis. The biopsy specimens showed changes compatible with asbestosis in 75% of the suspected cases and in 86% of those in which asbestosis was the final diagnosis. In the mixed-dust group pneumoconiosis was confirmed in 67% and 80%, respectively. In the diagnosis of silicosis an open biopsy is probably more reliable than a percutaneous one, particularly if radiographic changes are minimal. Histological changes in the needle biopsy specimen were compatible with silicosis in only 36% of the suspected cases and in 63% of those in which the final diagnosis was silicosis.